Evaluation of Anti-PT Antibody Response after Pertussis Vaccination and Infection: The Importance of Both Quantity and Quality - Barkoff Alex-Mikael; Knuutila Aapo; Mertsola Jussi; He Qiushui (MDPI, 2022)
Pertussis toxin (PT) is considered the main virulence factor causing whooping cough or pertussis. The protein is widely studied and its composition was revealed and sequenced already during the 1980s. The human immune system creates a good response against PT when measured in quantity. However, the serum anti-PT antibodies wane rapidly, and only a small amount of these antibodies are found a few years after vaccination/infection. Therefore, multiple approaches to study the functionality (quality) of these antibodies, e.g., avidity, neutralizing capacity, and epitope specificity, have been investigated. In addition, the long-term B cell memory (Bmem) to PT is crucial for good protection throughout life. In this review, we summarize the findings from functional PT antibody and Bmem studies. These results are discussed in line with the quantity of serum anti-PT antibodies. PT neutralizing antibodies and anti-PT antibodies with proper avidity are crucial for good protection against the disease, and certain epitopes have been identified to have multiple functions in the protection. Although PT-specific Bmem responses are detectable at least five years after vaccination, long-term surveillance is lacking. Variation of the natural boosting of circulating Bordetella pertussis in communities is an important confounding factor in these memory studie